Staff Week as a Modernization Tool in Translator Training Programs: Experience of Cooperation in the Erasmus + - V. A. Mityagina; E. Yu. Novikova; K. Wenzl (Высшее образование в России)
Translator training in the coordinates of the global educational space implies an integrative approach to unification and at the same time extension of theoretical, methodological and didactic approaches. At the same time, the search for effective ways and tools of interaction is carried out at different levels – academic, professional communities, individual persons, since the profession of a translator implies communication without borders, networking and constant expansion of the circle of partnerships. This article analyzes the effectiveness of one of the current tools for interuniversity cooperation in the format of Staff Week internships, integrated into the Erasmus + academic mobility program, in the focus of its validity and functionality in training translators. The study provides an analysis of domestic and foreign scientific and educational works on the scientific, didactic potential of the program, a review of the current state of affairs in the field of intercollegiate cooperation within Erasmus + on the example of the Russian university – Volgograd State University and the German university – International University SDI Munich. These universities have been developing partnership relations since the 90s, however, Erasmus has been cooperating with them recently and quite successfully. The material of the study is an overview of the structure and content of the Staff Week internships of Volgograd State University teachers at SDI Munich. The Intercultural component of interaction is effectively manifested in the optimization of didactic models in the partner university, updating of curricula, expanding the horizons of joint projects, which certainly contributes to improving the quality of educational services in the field of translation and promotes the integration of education in general. The results of this research can be useful for the organization of the educational process in university educational programs in the areas of training specialists in the field of translation and intercultural communication.